Critical success factors for e-learning implementation in Egyptian public universities: a stakeholders' analysis - AlShabrawy, Hoda Salaheddin (AUC Knowledge Fountain, 2015)
Higher education is witnessing major change worldwide and new methods of learning are emerging. Modern technologies are affecting the way educational institutions address learning challenges through presenting innovative solutions. E-learning is a form of education to which attention has increased worldwide. Flexibility provided by e-learning is makes it possible for universities around the world to enroll an increased number of students to meet the needs of all learners. The higher education system in Egypt faces several challenges which hinder it from development. It has become important for Egypt to strive to use new technologies to develop and strengthen higher education. Nevertheless, the take-up and use of e-learning in Egypt is still in its early stages and many difficulties and challenges need to be addressed in order for e-learning to be widely adopted. The present thesis studies the current situation of e-learning implementation and adoption at Egyptian public universities. The study analyzes the prospects of benefiting from e-learning in Egypt to minimize the problems facing the higher education system. The study further points out challenges that hinder the take up of e-learning and highlights the critical success factors needed in order to implement e-learning successfully in Egypt. Qualitative data was collected through conducting face-to-face semi-structured interviews with 21 top management officials, strategic planners, information technology experts, instructional designers, and professors teaching e-learning courses from different public universities. The thesis concludes with a set of policy recommendations in order to successfully implement e-learning in the higher education system.